Capturing patient experience: does quality-of-life appraisal entail a new class of measurement? - Carolyn E. Schwartz; Roland B. Stark; Bruce D. Rapkin (SpringerOpen, 2020)
Abstract Background Two decades of research on quality-of-life (QOL) appraisal have demonstrated links between patient experience and health outcomes and have accounted for both intra-individual change and inter-individual differences in a wide range of research contexts. The present work investigates patterns across diagnostic and demographic groupings to demonstrate how population-specific circumstances drive the structure of QOL appraisal. Methods This secondary analysis (N = 6448) utilized data from six patient groups: spine surgery, multiple sclerosis, heterogeneous chronically ill, heterogeneous cancer, bladder cancer, and human immunodeficiency virus (HIV). We explored patterns of inter-item correlation across patient samples, using items from the Standards of Comparison and Sampling of Experience subsections of the QOL Appraisal Profile v1 and v2. Similar matrices were compared by demographic characteristics. Results Patterns of inter-item correlations for Standards of Comparison items varied sharply across disease groups and racial groups while being similar across age, gender, and education levels. Inter-item correlation matrices for Sampling of Experience items revealed marked differences among disease groups and educational and racial categories but were similar across age and gender groups. Conclusions Appraisal parameters showed evidence of shared and unique aspects across samples and circumstances, findings which make sense in light of sample differences in health status and demographic influences. Tools to assess patient experience and meaning may be best understood as idiometric instruments. We discuss their distinctions from psychometric and clinimetric tools at theoretical, statistical, and applied levels.